Navigating entrepreneurial terrain: The role of technology readiness and gender in shaping intentions - Haryanto, Haryanto; Haryono, Tulus; Tanding Suryandari, Retno; Sugiarto, Catur; Suryanadi, Pram; Rawidyo Putro, Tetuko; Budiwati, Christiyaningsih (Journal of Innovation in Business and Economics, 2023)
The pervasive influence of information technology across various life sectors, particularly in the business realm, has prompted this study to investigate the impact of technology readiness on entrepreneurial intentions within a student context. A purposive sampling method was employed to select a sample comprising 213 college students, and Structural Equation Modeling (SEM) was utilized to assess the interrelationships among the study's constructed variables. The findings underscore the significant impact of technology readiness on attitudes, which, in turn, plays a pivotal role in shaping entrepreneurial intentions. Furthermore, the research highlights the influential roles of subjective norms and perceived behavioral control in the formation of entrepreneurial intentions. Conversely, results from the Multi-Group Analysis (MGA) do not support the gender variable as a moderating factor. However, a noteworthy revelation emerges from the bootstrapping analysis, unveiling gender-based differences in the influence of subjective norm variables on entrepreneurial intentions when comparing male and female groups.